2017
DOI: 10.1177/0022219417690354
|View full text |Cite
|
Sign up to set email alerts
|

Conservation Abilities, Visuospatial Skills, and Numerosity Processing Speed: Association With Math Achievement and Math Difficulties in Elementary School Children

Abstract: The aim of the present study was to investigate the associations between elementary school children's mathematical achievement and their conservation abilities, visuospatial skills, and numerosity processing speed. We also assessed differences in these abilities between children with different types of learning problems. In Study 1 ( N = 229), we investigated second to fourth graders and in Study 2 ( N = 120), third and fourth graders. Analyses revealed significant contributions of numerosity processing speed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 50 publications
1
24
0
4
Order By: Relevance
“…Nonetheless, concrete-operational thinking represents an important prerequisite of formal thinking (Inhelder and Piaget, 1958;Powell and Kalina, 2009). It is associated with a range of learning outcomes and academic achievement (Jordan and Brownlee, 1981;Hattie, 2009), such as maths fluency and maths achievement (conservation ability; Arlin, 1981;Cooper and Schleser, 2006;Ramos-Christian et al, 2008;Krajewski and Schneider, 2009;Wubbena, 2013;Lambert and Spinath, 2018), as well as reading comprehension and reading achievement (conservation and classification ability; Arlin, 1981;Cartwright, 2002;Colé et al, 2014;Cartwright et al, 2017). At the same time, differences in the ability of concrete-operational thinking become clear, as e.g., students with learning disabilities show lower levels of concrete-operational thinking than their peers (Wember, 1986;Riley, 1989;Fakouri, 1991).…”
Section: Concrete-operational Thinkingmentioning
confidence: 99%
“…Nonetheless, concrete-operational thinking represents an important prerequisite of formal thinking (Inhelder and Piaget, 1958;Powell and Kalina, 2009). It is associated with a range of learning outcomes and academic achievement (Jordan and Brownlee, 1981;Hattie, 2009), such as maths fluency and maths achievement (conservation ability; Arlin, 1981;Cooper and Schleser, 2006;Ramos-Christian et al, 2008;Krajewski and Schneider, 2009;Wubbena, 2013;Lambert and Spinath, 2018), as well as reading comprehension and reading achievement (conservation and classification ability; Arlin, 1981;Cartwright, 2002;Colé et al, 2014;Cartwright et al, 2017). At the same time, differences in the ability of concrete-operational thinking become clear, as e.g., students with learning disabilities show lower levels of concrete-operational thinking than their peers (Wember, 1986;Riley, 1989;Fakouri, 1991).…”
Section: Concrete-operational Thinkingmentioning
confidence: 99%
“…Hasil penelitian ini sejalan dengan penelitian yang telah dilakukan sebelumnya yang menunjukkan bahwa kemampuan konservasi anak umumnya masih rendah (Funny, 2014;Ramlah, 2015;Arumsari et al, 2014;Lambert & Spinath, 2018;Ashley-Smith, 2016). Dalam penelitian ini lebih dari 50 persen anak usia 7-8 tahun di kabupaten Manggarai (mengacu pada tabel 1) tergolong non-konserver.…”
Section: Hasil Dan Pembahasanunclassified
“…Ketiga tahap pencapaipan konservasi ini sesuai dengan perkembangan kognitif anak. Seiring pengalaman dan kematangan, kemampuan konservasi sederhana yang dimiliki anak pada awal sekolahnya dapat membantunya dalam memahami konsep konservasi yang lebih kompleks (Lambert & Spinath, 2018 (Makur, Prahmana & Gunur, 2018;Mann, 2014;Nafiah, Suyanto, & Yogyakarta, 2014). Selain itu pemahaman terhadap konsep matematika akan lebih mudah dipahami apabila pembelajaran matematika disajikan dengan mengaitkan konsepnya dengan masalah kehidupan sehari-hari (Tik, 2014;Crowley, 2015;Izzati, Ahmad, & Abu, 2010 Novitasari, 2016).…”
unclassified
“…PS deficits have been most commonly associated with specific reading disorder (RD) 12,[15][16][17] , though one study found that the relationship between reading decoding and low PS disappears after the age of eight 3 . Though specific math disorder (MD) is less commonly studied with PS, some studies have found significant PS deficits in children with MD when compared to their typically-developing counterparts 11,18,19 , while others have found no significant differences in PS scores 20,21 .…”
Section: Introductionmentioning
confidence: 99%
“…Of note, inattention has been specifically associated with PS deficits when treated as a dimensional symptom, as well as reading deficits [41][42][43] . Finally, it is worth noting that comorbidity amongst MD, RD, and ADHD has also been associated with low PS, and the relationships between these deficits continue to be explored 19,[22][23][24][25][26] .…”
Section: Introductionmentioning
confidence: 99%